Bergey's manual of determinative bacteriology - Holt, John G (Williams and Wilkins, 1994)
Based on the data contained in the four-volume Bergey\'s Manual of Systematic Bacteriology, BMDB-9 also includes new genera and species, new combinations, and new taxa published through the January 1992 issue of the IJSB. Users will find short general descriptions that encompass all organisms by Groups; shape and size, Gram reaction, other pertinent morphological features, motility and flagella, relations to oxygen, basic type of metabolism, carbon and energy sources, habitat and ecology. BMDB-9 also includes discussions of difficulties in identification, keys or tables to genera and species, genus descriptions, synonyms, other nomenclatural changes, and numerous illustrations.
Keywords: bakteriologické techniky; Bacteriological Techniques; mikrobiologie, lékařská mikrobiologie; bakteriologie; Bacteria; Bacteriology